The International nature of Corruption in the Kingdom of Yugoslavia - Božović, Jovan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The social context in which the Kingdom of Yugoslavia was created—marked by the devastation of the preceding war—quickly led to political polarization over fundamental questions of state organization. Despite this, the establishment of state institutions with democratic potential offered some hope for strengthening anti-corruption efforts. However, it became evident that upholding the rule of law and effectively combating corruption required far more: either radical political reform or a complete systemic transformation. Behind the Našica affair, we can identify structural causes underlying the observed patterns of corruption. Specifically, the economic system of the Kingdom of Yugoslavia was designed in such a way that conducting business was virtually impossible without administrative support. Forests, for example, were directly controlled by the state—a system that was neither efficient nor effective but instead allowed numerous public officials and civil servants to extract corrupt rents. Moreover, the Našica affair highlighted key systemic flaws: the absence of a comprehensive legal framework to combat corruption, including regulations on lobbying. Notably, the body of so-called corruption crimes defined in the 1929 Criminal Code did not criminalize abuse of office or influence peddling by members of parliament during the legislative process. Ultimately, the inconsistent enforcement of existing laws—despite at least a minimal degree of political will to fight corruption—meant that the Našica affair failed to reach a meaningful judicial conclusion.